Imej Tumbuhan Dalam Peribahasa Tamil : Suatu Kajian Semantik Inkuisitif - Tangaprabu, Murthy (Universiti Malaysia Sarawak (UNIMAS), 2017)
Tamil proverbs are the art of spoken literature among the Indian tribe. These proverbs are created based on their contemplation towards the beauty and uniqueness of the nature and also their surroundings. They believed all these components of nature always have something to tell, be it directly, indirect or both. In conjunction with that, this study aspires to identify the implicit meanings behind the usage of Tamil proverbs which involve the aspects of nature; plants. This study also focuses on how the culture affects the creation of the Tamil proverbs which takes plants in count, to provide literal understanding to a proverb. This study also counts in inquisitive meanings in order to provide a better understanding about Tamil proverbs. Since this is a.qualitative study, a number of four informants were interviewed to obtain the data. This study sequels a positive outcome where it is confirmed that the proverbs that exist are created from the surroundings of the native Tamils, especially plants. Every proverb from the previous people has a strong cognitive connection with implicit meanings where they convey messages figuratively. Conclusively, this study portrays the high order of thinking skills among the Indian community which establish their way of cognition in Tamil; in plants.